2004
DOI: 10.1021/jp045414j
|View full text |Cite
|
Sign up to set email alerts
|

Formation and Characterization of the (η2-N2)Sc(H)OH and (η-NN)xSc(H)OH (x = 1, 2) Complexes in Solid Argon

Abstract: Hydrido scandium hydroxide dinitrogen complexes, (eta2-N2)Sc(H)OH and (eta1-NN)xSc(H)OH (x = 1, 2), have been prepared by the reactions of laser-ablated scandium atoms with H2O/N2 mixtures in solid argon. The end-on bonded (eta1-NN)xSc(H)OH (x = 1, 2) complexes were formed spontaneously on annealing, whereas the side-bonded (eta2-N2)Sc(H)OH complex was generated on broad-band irradiation. These complexes were characterized by infrared absorption spectroscopy as well as density functional theoretical calculatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
8
1

Relationship

6
3

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…The cyclic Sc(μ-N) 2 Sc absorptions were observed to increase when subjected to annealing at 25 and 35 K; however, the N 2 -ligated (NN) x Sc(μ-N) 2 Sc(NN) x complex absorptions were barely observed, even after high-temperature annealing. Two new absorptions, at 653.7 and 590.6 cm -1 , appear together when subjected to annealing at 25 K, and increase markedly when subjected to annealing at 35 and 43 K. Very weak absorptions due to ScO, [ScO(Ar) 5 ] + , and ScO 2 - were also observed. , In the N−N stretching frequency region (not shown in Figure ), no obvious absorptions except weak ScNN and (η 1 -NN)Sc(H)OH (1884.4 cm -1 ) absorptions were observed 2 IR spectra in the 680−570 cm -1 region from co-deposition of laser-evaporated Sc atoms and clusters with isotopic labeled N 2 in excess argon.…”
Section: Resultsmentioning
confidence: 94%
“…The cyclic Sc(μ-N) 2 Sc absorptions were observed to increase when subjected to annealing at 25 and 35 K; however, the N 2 -ligated (NN) x Sc(μ-N) 2 Sc(NN) x complex absorptions were barely observed, even after high-temperature annealing. Two new absorptions, at 653.7 and 590.6 cm -1 , appear together when subjected to annealing at 25 K, and increase markedly when subjected to annealing at 35 and 43 K. Very weak absorptions due to ScO, [ScO(Ar) 5 ] + , and ScO 2 - were also observed. , In the N−N stretching frequency region (not shown in Figure ), no obvious absorptions except weak ScNN and (η 1 -NN)Sc(H)OH (1884.4 cm -1 ) absorptions were observed 2 IR spectra in the 680−570 cm -1 region from co-deposition of laser-evaporated Sc atoms and clusters with isotopic labeled N 2 in excess argon.…”
Section: Resultsmentioning
confidence: 94%
“…Matrix isolation spectroscopy plays an important role in preparation and characterization of simple transition metal dinitrogen complexes, which have provided a wealth of insight into the structure and bonding of such model complexes. The results show that most of mononuclear transition metal dinitrogen complexes are end-on bonded. However, different binding modes have been observed in some dinuclear as well as divalent transition metal dinitrogen complexes. In this paper, we report a combined matrix isolation infrared spectroscopic and theoretical study of tantalum dioxide−dinitrogen complexes. We will show that TaO 2 can coordinate up to three dinitrogen molecules in forming dinitrogen complexes, and both the side-on and end-on coordination modes are observed, which are found to be photointercovertable.…”
Section: Introductionmentioning
confidence: 99%
“…Matrix isolation studies on the reactions of bare transition metal atoms with dinitrogen indicate the formation of the end-on bonded dinitrogen complexes. Experiments with laser-ablated metal atoms also gave evidence for the formation of side-on bonded complexes, presumably from the excited state metal atom reactions. , Some transition metal dimers are more reactive than the metal atoms toward dinitrogen. It was found that the Sc 2 and Ti 2 dimers reacted spontaneously with dinitrogen to form the cyclic Sc 2 N 2 and Ti 2 N 2 compounds in which the N–N triple bond is completely cleaved. , The reactions of transition metal oxide molecules with N 2 in solid argon have also been reported. The results showed that transition metal monoxides such as ScO, TiO, MnO, and FeO and dioxides, including TaO 2 and CrO 2 , are able to react with dinitrogen in forming dinitrogen complexes in solid argon. Both the side-on and end-on coordination modes were observed, which were found to be photointercovertable in selected systems. In this paper, the reactions of titanium monoxide and dioxide molecules with dinitrogen were reinvestigated using the more inert neon matrix to minimize the matrix effect.…”
Section: Introductionmentioning
confidence: 99%